The power of truth-drive propaganda: a rhetorical criticism of governor Ajimobi's political slogan: "ki oyo le da'a ajumose gbogbo wa ni" (2014)
"Oration is a major factor that determines the effectiveness of political slogans. In its absence however, some other factors must account for the success of a political slogan. Adapting a combination of the rhetorical situation and the pentad, this study presents a rhetorical criticism of ‘ki Oyo lee da’a, ajumose gbogbo wa ni’, slogan of Governor Abiola Ajimobi of Oyo state. Kenneth Burke’s theories of identification and equipment for living constitute the theoretical framework. The governor carefully and successfully devised the ajumose slogan with strong cultural and democratic appeals that resonate also with acceptable practice in global development activities. These kinds of appeals are more effective in an ideologically incoherent political context where people resort to ethnic biases in making vital political decisions. The truth appeal in the slogan is made to serve political propagandistic purposes of the governor which is an instance of symbol misuse. Finally, the slogan engages the public in a sustained but one-sided conversation which attains amplification which the governor abuses in presenting the slogan as an answer to every question and a counter-argument for every argument that might be raised against him. "